Die me a river - Swanson, Denise (Swanson, Denise. Welcome back to Scumble River., 2018)
School psychologist Skye Denison-Boyd had hoped that her maternity leave would be at least a little relaxing, but when she and her husband, Wally, meet with the priest to discuss their newborn twins' christening, an explosion at the nearby bowling alley rocks the rectory. And although the business was closed at the time of the blast, there's a body inside. As police chief, Wally is inevitably drawn into the investigation, which seems to indicate that foul play is afoot again in Scumble River, and Skye can't help but do a bit of her own sleuthing. But the clues come fast and furious, ranging from an odd new stranger in town to animosity toward the gambling machines that had recently been installed at the bowling alley, and Skye finds herself wondering if this could be the puzzle that stumps her for good.